Relations between evapotranspiration and grain yield of corn - Medeiros, Sandro L. P.; Westphalen, Sérgio L.; Matzenauer, Ronaldo; Bergamaschi, Homero (Pesquisa Agropecuaria Brasileira, 1991)
A study was performanced to evaluate the possibility of corn grain yield prediction through relations between the relative grain yield (actual yield/maximum yield) and the actual evapotranspiration/maximum evapotranspiration index, at seven growth stages and at all the crop cycle, as well as to identify the most critical periods to water deficits. The data were obtained at the experimental station of Taquari, in Depressão Central region of Rio Grande do Sul, Brazil (29o48’15" latitude, 51o49’30"W longitude, and 76 m altitude), during seven growing seasons and at different sowing dates. It was shown that the most sensible period to water deficits was the one from ten days before tasseling to ten days after silking. For this period, the relation grain yield (ŷ) corn may be estimated from the equation ŷ = 0,663x2 + 0,154x + 0,223, with a determination coefficient r2 = 0,74. For all the crop cycle, the equation ŷ = 1,611x2 + 1,220 x + 0,537 corn may be used, although with less precision (r2 = 0,53). For the other periods of the corn cycle, there was lower association between grain yield and water deficits.